Analysis of the Determinant Effects Stress of Students that Working on Thesis - Supriyono; Luqita Romaisyah; Alfiandi Imam Mawardi (Nusantara Science and Technology Proceedings)
Demands on the quality of education increasing continually, the government is promoting a high standard to deal with industry 4.0. One of the problems in terms of education phases is the thesis that problems occur in the work of the thesis triggers the stress of students who can inhibit thesis completion. This research aims to link the relationship between self-efficacy and self-disclosure and moderator variables namely emotional quotient (EQ) with student stress when working on the thesis. This study aims to link the relationship between self-efficacy and self-disclosure and moderator variables namely emotional quotient (EQ) with student stress when working on the thesis. This research also uses the quantitative Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach. The population in this study is students who have taken the thesis for more than one year. The results of this study indicate in descriptive that (1) self-efficacy and EQ have a significant influence on student stress that show how important those variables influence student stress (2) On the other side, self-disclosure hasn’t an effect to strengthen student stress that insignificantly effects (3) The role of the lecturer as an important supervisor and other lecturing media will be determining and influencing student stress (4) There are several solutions to decrease student stress.